Monumental cares sites of history and contemporary art - Widrich, Mechtild (Manchester University Press, 2023)
Monumental cares rethinks monument debates, site specificity and art activism in light of problems that strike us as monumental or overwhelming, such as war, migration and the climate crisis. The book shows how artists address these issues, from Chicago and Berlin to Oslo, Bucharest and Hong Kong, in media ranging from marble and glass to postcards, graffiti and re-enactment. A multidirectional theory of site does justice to specific places but also to how far-away audiences see them. What emerges is a new ethics of care in public art, combined with a passionate engagement with reality harking back to the realist aesthetics of the nineteenth century. Familiar questions can be answered anew: what to do with monuments, particularly when they are the products of terror and require removal, modification or recontextualisation? And can art address the monumental concerns of our present? -- .
Keywords: Geschichte 1950-2020; Klimaänderung; Denkmal; Krise; Migration; Krieg; Öffentlicher Raum; Kunst; Gesellschaft